The garden party and other stories (Art of the Story, ,, 2009)
Written during the final stages of her illness, this was Katherine Mansfield's last collection of stories to be published in her lifetime. Comprising fifteen stories, this edition comes with an introduction and notes by Lorna Sage.
At the bay , The garden party , The daughters of the late Colonel , Mr and Mrs Dove , The young girl , Life of Ma Parker , Marriage á la Mode , The voyage , Miss Brill , Her first ball , The singing lesson , The stranger , Bank holiday , An ideal family , The lady's maid.

The friendly postman: the art of Van Gogh (Stories of art, , 1, 2016)
The story about the Dutch artist, Vincent Van Gogh, who is famous for his brightly colored paintings of sunflowers and wheatfields. Van Gogh worked hard at his art, but had little success during his lifetime. His only supporter was his younger brother, Theo. He loved and valued Vincent's paintings more than anyone else, and wrote to him regularly. The story imagines Van Gogh's relationship with his postman, Joseph Roulin, who delivered Theo's letters, and how a quiet friendship might have grown between the two men. Contains biographical information about the artist at the end of story.

Whatever Happened to Interracial Love?: Stories (Art of the Story, ,, 2016)
A collection of newly discovered and never-before-published stories by the late Kathleen Collins, a brilliant yet little-known African American writer, artist, and filmmaker. Exuberant, poignant, perceptive, and full of grace, these sixteen stories by Kathleen Collins explore deep, far-reaching issues-relating to race, gender, family, and sexuality-that shape the ordinary moments in our lives. Collins's work masterfully blends the quotidian and the profound in a personal, intimate way, seamlessly integrating the African American experience into her characters' lives and creating rich and devastatingly familiar characters who transcend symbolism. In "The Uncle," a young girl who idolizes her handsome uncle and his beautiful wife makes a haunting discovery about their lives. In "Only Once," a woman reminisces about her charming daredevil of a lover and his ultimate-and final-act of foolishness. And in the title story, a recent college graduate realizes the limits of the civil rights movement-and the personal and romantic consequences it holds for her. Both contemporary and timeless, Whatever Happened to Interracial Love? is a major and long- overdue addition to our literary canon.

The general zapped an angel: stories (Art of the story, ,, 2019)
"In The General Zapped an Angel, featuring nine supremely entertaining fantasy and science fiction tales, a Vietnam general shoots down what appears to be an angel; a man sells his soul to the devil for a copy of the next days Wall Street Journal; and a group of alien beings bestow a mouse with human thought and emotion."-- Jacket flap.
The general zapped an angel --, The mouse --, The vision of Milty Boil --, The Mohawk --, The wound --, Tomorrow's Wall Street Journal --, The interval --, The movie house --, The insects.